2016
DOI: 10.18632/oncotarget.13673
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of salt-inducible kinase 1 (SIK1) is mediated by RNF2 in hepatocarcinogenesis

Abstract: Our previous study reported that down-regulation of SIK1 accelerates the growth and invasion of hepatocellular carcinoma (HCC). However, the underlying mechanism leading to SIK1 down-regulation in HCC largely remains to be determined. Herein, we demonstrated that RNF2 expression is negatively correlated with SIK1 levels in HCC tissues. Kaplan-Meier analysis of tumor samples revealed that high RNF2 expression with concurrent low SIK1 expression is associated with poor overall survival. The down-regulation of RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…Since we have shown that SIK also binds to TGFβRI and together with Smurf2 promotes degradation of TGFβRI [ 23 ], we consider favorably the possibility of involvement of Smurf E3 ligases in the degradation mechanism of Par3, opening up an exciting scenario of coordinate TJ and polarity regulation by ubiquitination. On the other hand, RNF2 that ubiquitinates and degrades SIK [ 54 ], may also be involved in Par3 degradation, assuming that an unknown mechanism enforces cytoplasmic residence of RNF2; the latter is compatible with our observations that support coordinate degradation of SIK and Par3 (Figure 3 , 4 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since we have shown that SIK also binds to TGFβRI and together with Smurf2 promotes degradation of TGFβRI [ 23 ], we consider favorably the possibility of involvement of Smurf E3 ligases in the degradation mechanism of Par3, opening up an exciting scenario of coordinate TJ and polarity regulation by ubiquitination. On the other hand, RNF2 that ubiquitinates and degrades SIK [ 54 ], may also be involved in Par3 degradation, assuming that an unknown mechanism enforces cytoplasmic residence of RNF2; the latter is compatible with our observations that support coordinate degradation of SIK and Par3 (Figure 3 , 4 ).…”
Section: Discussionsupporting
confidence: 87%
“…Twist1 would also transcriptionally repress the SIK gene, explaining the low SIK expression in aggressive HCCs [ 53 ]. Furthermore, the low levels of SIK protein in aggressive HCC are maintained by the nuclear ubiquitin ligase RNF2, a subunit of the Polycomb co-repressor complex 1 [ 54 ]. Additional studies in lung and kidney epithelial cells support the nuclear actions of SIK.…”
Section: Discussionmentioning
confidence: 99%
“…Another example of a relatively under-studied transcript up-regulated by YM-155, is salt inducible kinase 1 (SIK1) which is evident at both time points [+5.04, p<0.001, 8 h/ +8.06, p<0.001, 20 h]. Like FOSB, SIK1 has been reported as a tumor suppressor capable of halting tumor growth, metastasis and rendering greater overall survival rates (44,45). Likewise, numerous studies are now reporting that a reduction of SIK1 is associated with drug/adiation resistance, aggressive tumor pathologies and greater likelihood of epithelial-mesenchymal transition (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly several studies published up to now described worsening of prognoses with increased RNF2 expression in cancers of pancreas [ 14 ], esophagus [ 15 ], liver [ 16 ], urinary bladder [ 17 ] and ovary [ 18 ]. It is possible that spectrum of genes actively modulated by RNF2 changes in different cell types [ 10 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%